Understanding the Meanings of Ownership - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Expanding women’s asset ownership is key for improving gender equality and promoting economic development and well-being. A widespread challenge in data collection is that ownership can have different meanings across contexts, particularly regarding which components of the bundle of rights comprise ownership. Yet, surveys often implicitly assume that all rights are held by the same person. This tool, Understanding the Meanings of Ownership, allows us to elicit responses regarding subjective assessments of what ownership entails by presenting different scenarios in which the main premise is a woman owning a particular asset, but scenarios differ on the rights that women have over the asset. The multiple questions aim to assess how the answers may vary by type of asset and women’s status in the household (living with a partner, living with in-laws, living with her parents). To fully understand individuals’ understanding of ownership, it is useful to have this tool alongside modules that solicit information on individual’s ownership of the asset. This data study includes following files. 1. A survey document (including implementation guidelines) 2.Two files, CAPI_Choices and CAPI_Survey, along with the accompanying help files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.